2004
DOI: 10.1007/s00198-004-1786-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density at the distal radius, but not at the lumbar spine or the femoral neck, in Japanese type 2 diabetic patients

Abstract: The purpose of this study is to assess the association between type 2 diabetes and bone mineral density. This study included 145 Japanese patients (64 men and 81 women) with type 2 diabetes and 95 non-diabetic control subjects (41 men and 54 women) of similar age. We measured bone mineral density (BMD) at the sites with different cortical/cancellous bone ratio (lumbar spine, femoral neck, and distal radius) using dual-energy X-ray absorptiometry. BMD and Z score at the distal radius were significantly lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
5
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
6
47
5
6
Order By: Relevance
“…In addition, another possibilityis is that hypercholesterolemia itself might have been associated with higher bone turnover, and that reduced bone resorption found in our study might have only reflected the hypercholesterolemia improved by atorvastatin. Indeed, Koshiyama et al [25] have recently reported the possibility that hypercholesterolemia may be the main cause of abnormal bone metabolism in type 2 diabetes mellitus [26]. However, ∆NTx did not correlate with ∆TC, ∆TG, ∆LDL or ∆HDL in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…In addition, another possibilityis is that hypercholesterolemia itself might have been associated with higher bone turnover, and that reduced bone resorption found in our study might have only reflected the hypercholesterolemia improved by atorvastatin. Indeed, Koshiyama et al [25] have recently reported the possibility that hypercholesterolemia may be the main cause of abnormal bone metabolism in type 2 diabetes mellitus [26]. However, ∆NTx did not correlate with ∆TC, ∆TG, ∆LDL or ∆HDL in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Although the results remain somewhat controversial, [11][12][13], several studies found a more decreased BMD in patients with hypercholesterolemia [5] or a significant correlation between higher T-C and decreased BMD [6][7][8][9][10]. The possibility has been pointed out that hypercholesterolemia may be the main cause of abnormal bone metabolism in type 2 diabetes mellitus [5,27]. In addition, findings of an animal model study demonstrated that BMD was reduced in dyslipidemic mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whether lipids affect bone metabolism or not remains unclear thus far. However, Koshiyama et al [29] has recently reported the possibility that hypercholesterolemia may be the main cause of abnormal bone metabolism in type 2 diabetes mellitus [31]. In addition, both in vitro [32] and in vivo animal model studies [33] have also demonstrated some detrimental effects of lipids on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%